Depositional system, facies relations & reservoir characteristics of the Codell Sandstone, Colorado - Caraway, Donna C., author (Colorado State University. Libraries, 1990)
Deposition of the Turonian Codell Sandstone member of the Carlile Shale in north-central Colorado occurred along the western margin of the Cretaceous Epeiric Seaway. Abrupt and irregular facies relationships, gross sheet-like geometry with internal linear thickness trends, ichnofacies arrangement, and stratigraphic positioning suggest an inner shelf depositional origin. The Codell sandstone is initially sourced from Frontier equivalent delta systems in Wyoming during the 90 m.y.a. lowstand and is thought to represent the shelf component of a transgressive system tract which developed during the subsequent Niobrara cycle transgression. Storm processes operating along the inner shelf margin produced amalgamated storm sheet deposits of mid-late Turonian age. Deepening of the seaway restricted sediment influx onto the shelf which resulted in the cannibalization of the previously deposited shelf sediments. This change is marked by a marine flooding surface which separates the inner shelf sediments from the winnowed condensed section above. The silica or calcite-cemented uppermost bed of the Codell Sandstone represents the winnowed cap of a condensed section produced by this starved basin condition. Further deepening of the seaway placed the shelf floor beyond the reach of epidsodic storm processes and is marked by an abrupt lithologic transition into marine limestone deposits. This contact is referred to as a basinal sequence boundary. Production from the Codell Sandstone consists predominantly of Volatile Oil (GOR between 1000 and 5000 SCF/STBO) or Retrograde Gas Condensate (high API gravities and GOR between 5,000-100,000 SCF/STBO). Distribution of the production patterns depends primarily upon proximity to the faulted basin axis and thicker Codell Sandstone intervals. High GOR's created from the increased thermal gradients and fluid conductivity associated with the major basin-syncline bounding faults charged the system with solution driven gas. This produces an extremely mobile hydrocarbon environment. Because the Codell Sandstone is porous, but fairly impermeable, any reversal in dip direction or en-echelon arranged fault system updip from the down-dropped basin axis, provides a potential site for hydrocarbon accumulation. Correspondence of better production rates near fault systems in areas of slightly thicker sandstone indicates that the trapping mechanism is both a function of stratigraphy and structural relationships (a combination trap).Secondary porosity, developed from the dissolution of unstable framework constituents (plagioclase feldspar grains and rock fragments), allows hydrocarbon accumulation in an interval that would otherwise contain too much clay to be normally productive. The Codell Sandstone contains quartz grains and layered phyllosilicates (illite, illite/smectite, and chlorite). Subsidiary amounts of plagioclase feldspar and pyrite are also present. The abundant distribution of detrital clay in this interval, is due in part, to extensive bioturbation. Dissolution of calcite cement also enhances the development of secondary porosity in the Codell Sandstone. Extensive artificial fracturing techniques and weakly acidic delivery systems are the most efficient completion practices yet developed for this interval.
Includes plates.
Keywords: Sandstone -- Colorado; Facies (Geology); Geology, Stratigraphic